Police Recruitment and Retention for the New Millennium The State of Knowledge - Wilson, Jeremy M. (RAND Corporation, 2010)
Many police departments report difficulties in creating a workforce that represents community demographics, is committed to providing its employees the opportunity for long-term police careers, and effectively implements community policing. This book summarizes lessons on recruiting and retaining effective workforces.